Enzymatic Basis for Differentiation of Rhizobium into Fast- and Slow-Growing Groups - Drets, G. Martinez-De (1972)
Glucose-6-phosphate dehydrogenase, 6-phosphogluconate dehydrogenase, and other enzymes related to carbohydrate metabolism were studied in rhizobia. A nicotinamide adenine dinucleotide phosphate-6-phosphogluconate dehydrogenase was detected in strains of the fast-growing group of Rhizobium but not in strains of the slow-growing group. An enzymatic differentiation of rhizobia was established.